Aplikasi Metode Geolistrik Untuk Alat Monitoring Rembesan Limbah (Penelitian Model Fisik di Laboratorium) - Ngadimin Ngadimin; Gunawan Handayani (Institut Teknologi Bandung, 2001)
Geoelectrical method utilizes resistivity variation by measuring potential difference due to electrical current which is injected into the ground. The method can be imployed to characterize geological structure of the subsurface, to locate water reservoir, to monitor groundwater pollution and to explore geothermal reservoir. In this study, a laboratory physical model was used along with the geoelectric method as a means to monitor the pollutant transport in the sand of the model. The geoelectric method employed Wenner-Schlumberger configuration with electrode spacing of 5 cm.The result showed that the pollutant transport can be detected from the electrical resistivity variation. The addition conductive pollutant into the sand of the model caused the resistivity of the sand decreased, because the applied pollutant was conductive. After monitoring using five times measurement with pollutant interval application of 600 ml, the restivity measurement showed that the pollutant spreaded progressively at every measurement.